Multiracial Faculty Members' Experiences with Biculturalism. (23rd February 2021) - Harris, Jessica C.; Tanksley, Tiera
ABSTRACT: Framed by the concept of biculturalism this study explores how 26 Multiracial faculty members form and use biculturalism to navigate an academy steeped in monoculturalism, or the belief that all people should conform to a dominant white westernized worldview. Findings from this study suggest that many Multiracial faculty members form and use a unique form of biculturalism, borderlands biculturalism, to navigate postsecondary contexts. Study findings encourage the expansion of binary understandings of biculturalism, support the retention and success of a growing Multiracial faculty population in U.S. higher education, and guide implications for institutional transformation.